Effect of Exogenous Application of Nicotinic Acid on Genotypes of durum wheat (Triticum aestivum L.) under salt stress. - Salih, Sami M.; Abdulrraziq, Ahmed A. (Scientific Journal for Faculty of Science-Sirte University, 2024)
Two experiments were conducted (laboratory and pot). The laboratory experiment represented the tolerance of ten durum wheat genotypes (ACSAD) to levels (20, 30, 40%) of seawater. The pot experiment evaluated the efficiency of foliar spraying of nicotinic acid for three election genotypes of durum wheat (ACSAD 1671, 1711, and 1765), Under seawater levels (20, 30%). The results of the laboratory experiment showed that revealed significant (p < 0.05) differences in the genotypes’ response to salinity, the genotypes’ (1671, 1711and 1765), were superior in recording the best average germination percentage and seedling length compared to the other genotypes. The results of the pot experiment showed, after 80 days of sowing, under seawater irrigation conditions, decreases in (Plant height, Leaf area /plant, Spike length, number of spikes/plant, number of grains/spike, chlorophyll a, chlorophyll b, carotenoids, and total pigments) of the three durum wheat genotypes (ACSAD), compared to control. In contrast, foliar application of Nicotinic acid led to a significant decrease in a negative effect resulting from salinity for all vegetative growth parameters and the contents of photosynthetic pigments, especially with low concentrations of seawater. The (1671) genotype performed better than the (1711and 1765) genotypes in concern to high averages for all studied traits, under salinity and spraying with Nicotinic acid.